2019
DOI: 10.1088/1361-6463/ab1b7b
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance tuning of Ag nanoisland films using a CO2 laser

Abstract: We demonstrate that the surface plasmon resonance of Ag nanoislands (NIs) can be conveniently tuned through the laser power and irradiation time. For instance, the resonance wavelength of Ag NIs can be tuned from 548 nm to 452 nm under the 3 W laser power simply by varying the irradiation time from 5 sec to 2 min. Interestingly, the position-dependent optical absorption spectra and SEM analysis reveals that the Ag NIs gradually disappear from the irradiation center even at 3 W if the irradiation time is longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For OLED, a lot of research has focused on its transparent and conductive anodes [6][7][8][9][10], while little attention is paid to the cathode. At present, vacuum evaporation is the most common method for the preparation of silver or aluminium thin-film electrodes or other films [11][12][13]. As is well known, the thin-film electrodes prepared by vacuum evaporation possess high conductivity, good smoothness and extremely thin thickness; however, vacuum evaporation is also limited owing to insurmountable shortcomings such as expensive equipment, complicated vacuuming processes and low economic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For OLED, a lot of research has focused on its transparent and conductive anodes [6][7][8][9][10], while little attention is paid to the cathode. At present, vacuum evaporation is the most common method for the preparation of silver or aluminium thin-film electrodes or other films [11][12][13]. As is well known, the thin-film electrodes prepared by vacuum evaporation possess high conductivity, good smoothness and extremely thin thickness; however, vacuum evaporation is also limited owing to insurmountable shortcomings such as expensive equipment, complicated vacuuming processes and low economic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The laser beam diameter is ~10 mm at the position of the film with a Gaussian spatial profile. This means that the effective laser power density is different as a function of distance from the irradiation center [23]. Although it is technically possible to make the spatial profile of the laser beam to a nearly flat-top by introducing a commercial beam shaper we use the laser beam as it is in this work.…”
Section: Lasermentioning
confidence: 99%
“…Substrate heating with a CO2 laser is a versatile method to fabricate functional films, and it can be used not only to promote the reduction speed of metallic ions dispersed in a polymer matrix (so-called metal-polymer nanocomposite films) but also to induce solid-state dewetting of metallic films (socalled nanostructured metallic films). Indeed, we have recently shown that the irradiation of a non-focused CO2 laser beam onto thin metallic films for a few tens of seconds at a few W enables us to rapidly induce nanostructures in thin Au [22] and Ag films [23] with some notable differences between them.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, laser annealing with mid-infrared lasers, such as CO2 laser, do not necessarily need to be focused since their energy is mainly get absorbed by the substrate (typically quartz, silicon, or glass) which will rapidly be heated to high temperatures enough to initiate the solid-state dewetting process. Solid-state-dewetting of plasmonic metal films by a CO2 laser is already been reported for different applications (20,21,22).…”
Section: Introductionmentioning
confidence: 99%